Pendidikan Inklusi dalam Al-Qur’an Q.S Abasa Ayat 1-11 - Ade Ilfah; Ummi Nadrah Nasution; Asnil Aidah Ritonga; Mohammad Al Farabi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Thel background ils that elducatilon ils a basilc neleld for elvelry human belilng, but somel ilndilvilduals do not relcelilvel approprilatel elducatilon. Chilldreln who appelar wilth physilcal dilffelrelncels, abilliltilels and attiltudels that arel dilffelrelnt from humans iln gelnelral arel ofteln dilscrilmilnateld agailnst iln thel elducatilon systelm. Builldilng an attiltudel of tolelrancel willl bel elffelctilvel through ilnclusilvel elducatilon iln schools. Thel concelpt of ilnclusilvel elducatilon iln Ilslamilc telachilngs ils found iln thel Al-Quran, whilch elxplailns that humans on thils elarth welrel crelateld wilth varilous racels, elthnilciltilels, natilonaliltilels, gelndelrs, rellilgilons and dilffelrelnt abilliltilels to know, apprelcilatel and relspelct relgardlelss of elxilstilng dilffelrelncels. Iln thils scilelntilfilc work, thel relselarchelr useld thel lilbrary relselarch melthod by elxplorilng varilous relfelrelncels rellateld to thel topilc of dilscussilon, namelly analysils of thel concelpt of ilnclusilvel elducatilon iln thel Al-Quran, Surah Abasa velrsels 1-11. By undelrstandilng thel valuel of thel concelpt of ilnclusilvel elducatilon iln thel Koran, you can builld an attiltudel of socilal tolelrancel relgardlelss of dilffelrelncels. Whelrel elquiltablel elducatilon can elnablel all chilldreln to havel thel opportunilty to partilcilpatel fully iln relgular actilviltilels relgardlelss of any abnormaliltilels